2005
DOI: 10.1590/s1676-24442005000400010
|View full text |Cite
|
Sign up to set email alerts
|

Expressão imuno-histoquímica de c-erb-B2 e p53 em carcinomas gástricos

Abstract: Introdução: Em nosso meio, os carcinomas gástricos ainda são neoplasias bastante freqüentes e responsáveis por altas taxas de mortalidade. Recentemente, têm-se demonstrado a expressão de p53 e a amplificação do gene c-erb-B2 nos carcinomas gástricos. A relevância e o significado biológico destas alterações ainda não foram totalmente estabelecidos. Objetivo: Estudar as expressões imuno-histoquí-micas de p53 e c-erb-B2 em 482 casos de carcinomas gástricos. Material e métodos: Foram construídos três blocos de tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The HER2 expression was predominant in intestinal type, and they found no difference related to the anatomical site. Although that study showed results that are similar to ours, the frequency of HER2 expression may have been underestimated, since they used immunohistochemical grading score for breast cancer, in which the entire membrane should be stained, and not only the lateral and basolateral walls (5) . The second study conducted in Rio Grande do Sul by Cirne-Lima et al in 2009 identified HER2 positivity in 5.4% of 37 cases.…”
Section: Discussionsupporting
confidence: 61%
“…The HER2 expression was predominant in intestinal type, and they found no difference related to the anatomical site. Although that study showed results that are similar to ours, the frequency of HER2 expression may have been underestimated, since they used immunohistochemical grading score for breast cancer, in which the entire membrane should be stained, and not only the lateral and basolateral walls (5) . The second study conducted in Rio Grande do Sul by Cirne-Lima et al in 2009 identified HER2 positivity in 5.4% of 37 cases.…”
Section: Discussionsupporting
confidence: 61%
“…Data on HER2 expression in Brazilian patients with GC are very limited and there is a wide variation on published results. The first two studies ever conducted in Brazil found a HER2 overexpression rate of 12 and 5.4 %, including IHC 3+ and 2+ cases added together [ 23 , 24 ]. However, the grading score for breast cancer was used for HER2 status assessment, in which the entire cell membrane should be stained, and not only lateral or basolateral walls, which suggests underestimation of HER2 positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found an association between HER2 positive tumors and some pathological parameters, such as Laurén’s intestinal subtype ( P = 0.048), well to moderately differentiated tumors ( P = 0.004) and presence of lymphovascular invasion ( P = 0.031). The intestinal subtype has been proven to be the pathological feature most invariably associated with HER2 positivity in multiple studies [ 17 , 32 , 34 , 35 , 44 , 45 ], including the ToGA trial [ 30 ] and some with Brazilian patients [ 19 , 22 , 23 , 26 ]. Since HER2 positivity is expected to be found on intestinal-type tumors, we strongly encourage that, when dealing with a mixed-type tumor, areas showing an intestinal morphology should be selected for HER2 scoring.…”
Section: Discussionmentioning
confidence: 99%